2010
DOI: 10.1002/art.27450
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin stimulates prostaglandin E2 production in rheumatoid arthritis synovial fibroblasts

Abstract: Objective. Adipokines may influence inflammatory and/or immune responses. This study was undertaken to examine whether adiponectin affects the production of prostaglandin E 2 (PGE 2 ) by rheumatoid arthritis synovial fibroblasts (RASFs).Methods. Synovial tissue was obtained from patients with RA who were undergoing joint replacement surgery. Fibroblast-like cells from the third or fourth passage were used as RASFs. Expression of adiponectin receptor messenger RNA (mRNA) and protein was detected. PGE 2 (convert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 47 publications
(66 reference statements)
3
31
0
Order By: Relevance
“…It was also shown that adiponectin stimulates the production of interleukin-8 [29] and prostaglandin E 2 [30] by rheumatoid synovial fibroblasts, suggesting that adiponectin might act as a proinflammatory cytokine in rheumatoid inflammation. Adiponectin is secreted by not only adipocytes, but also in synovial fibroblasts in patients with rheumatoid arthritis [31].…”
Section: Discussionmentioning
confidence: 96%
“…It was also shown that adiponectin stimulates the production of interleukin-8 [29] and prostaglandin E 2 [30] by rheumatoid synovial fibroblasts, suggesting that adiponectin might act as a proinflammatory cytokine in rheumatoid inflammation. Adiponectin is secreted by not only adipocytes, but also in synovial fibroblasts in patients with rheumatoid arthritis [31].…”
Section: Discussionmentioning
confidence: 96%
“…Collectively, the present in vitro findings suggest that adiponectin protects the gastric mucosa from ethanol-induced injury, partially through activation of the COX-2/PGE 2 pathway in gastric epithelial cells. Kusunoki et al (18) showed that adiponectin-induced PGE 2 production is mediated partially by adiponectin receptors, AdipoR1 and AdipoR2 in rheumatoid arthritis synovial fibroblasts. Lee et al (22) showed that adiponectin activates AdipoR1 to increase the expression of COX-2 in mesenchymal progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin stimulates PGE 2 and IL-8 production in RA synovial fibroblast (93,94). In addition, it was also reported in RA synovial fibroblast that adiponectin is able to stimulate the production of IL-6, PGE 2 , vascular endothelial growth factor, and MMP-1 and MMP-13 (43,95).…”
Section: Adiponectin and Rheumatic Diseasesmentioning
confidence: 80%